The artistic interests of St. Vladimir University students: Theatre (1834-1863) - Самчук, Тарас (Київський національний університет імені Тараса Шевченка, 2017)
Research works devoted to the students of St. Vladimir University usually highlight either specific features of the educational process or some aspects of their everyday life. Student‘s artistic interest has been studied to the lesser extent. The article depicts the place of theatre in the life of St. Vladimir University students in the years 1834-1863. The author points out that the interest to the theatre developed under the influence of the region’s artistic tradition. Therefore specifics of Right- and Left-bank Ukraine’s theatrical life is analyzed in the article as well. Special attention is paid to Kyiv as the centre of theatrical life of the region. Performances in Kyiv theatre sustained a romantic tradition. The nobles were the main spectators of the Kyiv theatre. The peak of the theatrical season in Kyiv fell on the period of Сontract Fair which took place annually in the second half of January. Students were a part of the the city's theatre audience. It was an important part of their leisure. The students patterned after popular trends in the theatrical life of Kyiv in their amateur performances. Initially, they performed in their apartments. Afterwards, in the 1850's students started to play in the University’s hall and on the stage of the city theatre. Entrance to the student performances required a fee. The student actors received significant profits for their performances which were spent for the needs of the poorest fellows. The performances favoured the consolidation of the student corporation in the first half of the 1850’s. Soon afterwards the students’ theatre revealed a national divisions among students of Saint Vladimir University. Polish students were especially active. At the same time, participation in performances was a demonstration of the students’ self-expression and one of the ways to become popular among their colleagues and the public.

У статті досліджено значення театру в житті студентів Університету св. Володимира упродовж 1834-1863 рр. Висвітлено особливості театрального життя Лівобережної, Правобережної України та м. Києва, які були основою для формування студентських театральних смаків. З’ясовано, що відвідування міського театру та розігрування вистав як в домашніх умовах, так і для широкої публіки були звичним елементом дозвілля та повсякденного життя студентів Університету св. Володимира.
Мистецькі зацікавлення студентів Університету св. Володимира: театр (1834-1863)
Keywords: students; St. Vladimir University; theatre; студенти; Університет св. Володимира; театр